Flexible Working Arrangements Di Telkom Regional VI Kalimantan - Muhammad Miftah Ridho; Tomi Oktavianor (JURNAL BISNIS DAN PEMBANGUNAN, 2024)
The millennial generation tends to feel more comfortable at work if companies do not apply additional working hours that exceed the time they are supposed to work in a day. Applying flexibility at work can have a positive impact on mental health because employee stress levels can be reduced (Lewis & Humbert, 2010). In Indonesia, the application of a flexible working arrangement system is widely used by large companies, one of which is PT. Telekomunikasi Indonesia, Tbk. Telkom Indonesia has a definition of Flexible Working Arrangement or FWA, which is how employees work according to the needs and type of work being done. The purpose of enacting the Flexible Working Arrangement (FWA) regulations is to increase employee engagement and productivity, provide space for employees to achieve a work life balance, and strengthen employer branding so that they are able to attract and retain the best potentials needed by the company. The results of the study prove that Flexible Working Arrangements have been properly implemented at Telkom Regional VI Kalimantan, and are running effectively by fulfilling the following elements: Understanding FWA Principles, Supporting Facilities (internet access, online meeting channel, and others), Company Regulations, Commitments and Responsibilities (sharing information, knowledge, etc.), Having the same work goals that lead to agreements, Good Communication Ethics, Jobs that are able to be carried out online and do not require physical meeting